SINERGI ZAKAT PRODUKTIF DAN PEMBIAYAAN MIKRO SYARIAH DALAM PEMBERDAYAAN UMKM MUSTAHIK - Okfi Resti; Gebi Sintia Dwi (Islamic Banking & Economic Law Studies (I-BEST), 2026)
This study examines the synergy between productive zakat and sharia microfinance as an integrated strategy for empowering mustahik micro, small, and medium enterprises (MSMEs) in Indonesia. Using a qualitative library research method, this study analyzes theoretical frameworks, institutional models, and empirical evidence drawn from academic literature, regulatory documents, and reports from zakat and Islamic microfinance institutions. The findings reveal that productive zakat effectively builds the foundational capacity of mustahik through initial capital provision, entrepreneurship training, and intensive mentoring, thereby transforming them into bankable economic actors. Meanwhile, sharia microfinance serves as a growth catalyst by providing structured financing through interest-free Islamic contracts. When integrated through a three-phase synergy model encompassing capacity building, financial access, and sustainability, these two instruments create a regenerative Islamic social finance ecosystem capable of systematically breaking the cycle of structural poverty. Ultimately, this synergy facilitates the transformative journey of mustahik becoming muzakki, realizing Islam's vision of equitable wealth distribution and sustainable community welfare.